1970
DOI: 10.3329/bjar.v34i1.5757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated use of organic manures with chemical fertilizers in the rice-rice cropping system and its impact on soil health

Abstract: A field experiment was conducted during [2003][2004] at Bangladesh Agricultural University farm, Mymensingh to evaluate the suitability of different sources of organic materials for integrated use with chemical fertilizers for the BoroFallow-T. Aman rice cropping pattern. The experiment was set up in a randomized complete block design (RCBD) with three replications. Eighttreatments, formulated from organic manure and chemical fertilizers have been imposed. The treatment combinations are T 1 : control, T 2 : 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 3 publications
6
24
0
Order By: Relevance
“…Azim (1999) and Hoque (1999) reported that application of S from manure and fertilizers increased S content both in grain and straw. Ali et al (2009) also reported the similar results.…”
Section: Sulphur Content In Grain and Strawsupporting
confidence: 67%
“…Azim (1999) and Hoque (1999) reported that application of S from manure and fertilizers increased S content both in grain and straw. Ali et al (2009) also reported the similar results.…”
Section: Sulphur Content In Grain and Strawsupporting
confidence: 67%
“…Phosphorous balance was positive in all poultry manure treated plots irrespective of chemical source. These results were similar with the findings of some earlier works (Hossain et al, 2010 ;Ali et al, 2009). Table 3.…”
Section: Apparent Nutrient Balancesupporting
confidence: 93%
“…The increase in soil N and P after FYM application might be due to the direct addition of N and P through decomposition of the FYM added to the soil. The improvement in the soil available P with FYM addition could be attributed to many factors, such as the addition of P through FYM, and retardation of soil P fixation by organic anions formed during FYM decomposition [16]. Many authors associated the soil nutrient improvement role of FYM to a residual effect on succeeding crops.…”
Section: Soil Total Nitrogen and Available Phosphorusmentioning
confidence: 99%